1988
DOI: 10.1073/pnas.85.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Absence of three secreted proteins and presence of a 57-kDa protein related to irreversible arrest of cell growth.

Abstract: Absence of three secreted proteins and presence of a 57-kDa protein related to irreversible arrest of cell growth* (GI/S phase transition/senescent fibroblasts/ceil aging/conditioned medium/51-kDa protein) GEE CHING AND EUGENIA WANGtThe Rockefeller University, New York, NY 10021Communicated by Igor Tamm, September 16, 1987 ABSTRACT Two subsets of proteins from the conditioned medium of normal human diploid fibroblasts were detected by NaDodSO4/polyacrylamide gel electrophoresis analysis; the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
1992
1992

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…No direct evidence exists relating any of these changes to the mechanisms leading to senescence, as distinct from changes that occur as a result of senescence. Though a few potential biologic markers for senescent cells have been identified (Brooks et al, 1987;Ching and Wang, 1988), these markers have not been demonstrated to be absent from quiescent cells. Therefore, there remains a significant need for additional biologic markers that specifically identify the senescent phenotype.…”
mentioning
confidence: 99%
“…No direct evidence exists relating any of these changes to the mechanisms leading to senescence, as distinct from changes that occur as a result of senescence. Though a few potential biologic markers for senescent cells have been identified (Brooks et al, 1987;Ching and Wang, 1988), these markers have not been demonstrated to be absent from quiescent cells. Therefore, there remains a significant need for additional biologic markers that specifically identify the senescent phenotype.…”
mentioning
confidence: 99%
“…Although early studies using two-dimensional polyacrylamide gel electrophoresis identified a few proteins that appeared to be senescent cell-specific, the vast majority of the proteins detected were synthesized by both young and old fibroblasts (Sakagami et al, 1979;Engelhardt et al, 1979;Lincoln et al, 1984). Senescent-specific polypeptides of 57 kDa and 55 kDa have been described by Ching and Wang (1988) and Sottile et al (1987), respectively. West et al (1989) have suggested that these proteins may be forms of procollagenase, a protein overexpressed in senescent normal fibroblasts (West et al, 1989) and fibroblasts derived from Werner's syndrome patients (Bauer et al, 1986).…”
mentioning
confidence: 99%
“…If this were the case, one would expect genes, including those associated with the differentiated function of the cells, to be expressed differentially as the cells progress from phase I to phase 111. Several laboratories have identified proteins (Engelhardt et al, 1979;Wang, 1985;Sottile et al, 1987;Bayreuther et al, 1988;Ching and Wang, 1988;Cowles et al, 1989) or mRNAs (Lumpkin et al, 1986;Giordano and Foster, 1989) that are differentially expressed in low and high passage cells. However, the roles of these gene products in the differentiation or aging of the cells have not yet been fully defined.…”
mentioning
confidence: 99%